COVID-19 inpatient care performance in the unified health system, São Paulo state, Brazil: an application of standardized mortality ratio for hospitals' comparisons - Marla Presa Raulino Schilling; Margareth Crisóstomo Portela; Mariana Vercesi de Albuquerque; Mônica Martins (BMC, 2024)
Abstract Objective To evaluate the variation in COVID-19 inpatient care mortality among hospitals reimbursed by the Unified Health System (SUS) in the first two years of the pandemic in São Paulo state and make performance comparisons within periods and over time. Methods Observational study based on secondary data from the Hospital Information System. The study universe consisted of 289,005 adult hospitalizations whose primary diagnosis was COVID-19 in five periods from 2020 to 2022. A multilevel regression model was applied, and the death predictive variables were sex, age, Charlson Index, obesity, type of admission, Brazilian Deprivation Index (BrazDep), the month of admission, and hospital size. Then, the total observed deaths and total deaths predicted by the model's fixed effect component were aggregated by each hospital, estimating the Standardized Mortality Ratio (SMR) in each period. Funnel plots with limits of two standard deviations were employed to classify hospitals by performance (higher-than-expected, as expected, and lower-than-expected) and determine whether there was a change in category over the periods. Results A positive association was observed between hospital mortality and size (number of beds). There was greater variation in the percentage of hospitals with as-expected performance (39.5 to 76.1%) and those with lower-than-expected performance (6.6 to 32.3%). The hospitals with higher-than-expected performance remained at around 30% of the total, except in the fifth period. In the first period, 64 hospitals (18.3%) had lower-than-expected performance, with standardized mortality ratios ranging from 1.2 to 4.4, while in the last period, only 23 (6.6%) hospitals were similarly classified, with ratios ranging from 1.3 to 2.8. A trend of homogenization and adjustment to expected performance was observed over time. Conclusion Despite the study's limitations, the results suggest an improvement in the COVID-19 inpatient care performance of hospitals reimbursed by the SUS in São Paulo over the period studied, measured by the standardized mortality ratio for hospitalizations due to COVID-19. Moreover, the methodological approach adapted to the Brazilian context provides an applicable tool to follow-up hospital's performance in caring all or specific-cause hospitalizations, in regular or exceptional emergency situations.